Study of The Suitability of Tourism in the Lubuk Kertang Mangrove Forest Area, Langkat district, North Sumatra - Uswatul Hasan; Siti Mardiana; Syahbudin Hasibuan (Universitas Labuhanbatu, 2025)
Mangrove forests serve as a natural barrier against storm surges, tsunamis and coastal erosion. Their complex root systems dissipate wave energy, protecting coastal areas from the effects of severe weather.This article serves to evaluate the tourism potential of the Lubuk Kertang mangrove area, highlight its ecological and community significance, identify challenges, and propose sustainable management strategies to enhance ecotourism opportunities. Mangrove observation using the transectional square methodology was used to assess mangrove density. It involves establishing transect squares consisting of 20 units, each measuring 10 x 10 meters, starting from the coastal area and extending inland. The study found that the mangrove area consisted mainly of Avicennia marina species, with a density of 1860 individuals per hectare (18.6 individuals per 100 m²). The tourism suitability index results for the Lubuk Kertang mangrove forest area were very high at 87.5%, categorizing it as “very suitable” for ecotourism development. This indicates a strong potential to attract tourists and promote sustainable tourism practices in the region